Transcriptome sequencing and metabolic pathways of astaxanthin accumulated in Haematococcus pluvialis mutant under 15% CO2. (March 2017) - Cheng, Jun; Li, Ke; Zhu, Yanxia; Yang, Weijuan; Zhou, Junhu; Cen, Kefa
Highlights: Transcriptome sequencing and annotation was performed on Haematococcus pluvialis . Astaxanthin metabolism of H. pluvialis was enhanced by gamma ray and 15% CO2 . Pyruvate and fatty acid metabolism were enhanced to support astaxanthin biosynthesis. Abstract: Transcriptome sequencing and annotation was performed on Haematococcus pluvialis mutant red cells induced with high light under 15% CO2 to demonstrate why astaxanthin yield of the mutant was 1.7 times higher than that of a wild strain. It was found that 56% of 1947 differentially expressed genes were upregulated in mutant cells. Most significant differences were found in unigenes related to photosynthesis, carotenoid biosynthesis and fatty acid biosynthesis pathways. The pyruvate kinase increased by 3.5-fold in mutant cells. Thus, more pyruvate, which was beneficial to carotenoids and fatty acid biosynthesis, was generated. Phytoene synthase, zeta-carotene desaturase, lycopene beta-cyclase involved in β-carotene biosynthesis in mutant cells were upregulated by 10.4-, 4.4-, and 5.8-fold, respectively. Beta-carotene 3-hydroxylase catalyzing conversion of β-carotene into astaxanthin was upregulated by 18.4-fold. The fatty acid biosynthesis was promoted because of the upregulation of acetyl-CoA synthetase and acetyl-CoA carboxylase, thus increasing astaxanthin esterification and accumulation in mutant cells.